Measurements of total gas content of an ice core from Mizuho Station, Antarctica - Kameda, Takao; Nakawo, Masayoshi; Nagoshi, Masayasu; Mae, Shinji (国立極地研究所, 1990)
Total gas content of an ice core, 700 m long drilled at Mizuho Station, East Antarctica (Mizuho core), has been measured by two methods. One method is the so called “melting method”, in which entrapped gas in an ice sample was collected in a gas burette by melting the sample in liquid. The other method, the “dry extraction method”, was also employed to measure gas content for small samples; gas was introduced into an evacuated container by crushing a sample. It was found that the total gas content of the Mizuho core increased almost linearly with decrease of depth from 600 to 180 m below the surface. Above 180 m, however, total gas content was much larger than the lower part of the ice core. This probably indicates that the ice sheet thickness has decreased since the gas was incorporated into the ice matrix located at about 180 m depth. application/pdf journal article